THE BEHAVIOR OF MAINTENANCE OF REMOVABLE PARTIAL DENTURES WITH THE INCIDENCE OF GINGIVITIS IN ELDERLY - Suharyono Suharyono; Helni Novianti Peluru; Etty Yuniarly (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: The incidence of missing teeth at the age of 56-64 years due to extraction in Poso Regency is 35.57%. The high incidence of tooth loss in the elderly will have an impact on decreasing various system functions. Replacement of teeth that have been lost in the elderly can be done using removable dentures. The use of dentures should be accompanied by good maintenance of dentures. The lack of maintenance of dentures will cause various health problems of the oral cavity, which one is gingivitis. Purpose: this study aims to analyze the relationship between the behavior of maintenance of removable partial dentures and the incidence of gingivitis in the elderly. Method: The type of this research was a quantitative study with an analytical observational approached using a cross sectional design. The variable in this research is the behavior of maintenance of removable partial dentures and the incident of gingivitis. The research was conducted at Posyandu Lansia in working area of Puskesmas Kawua on August 2022. The population of this research is 58 respondents. The samples of this research is 50 an calculated by slovin’s formula. Those samples were chosen using purposive sampling technique. The instrument that used in this research were collected from the behavior questionnaires and check sheet which were later analyzed using chi square test. Result: The behavior of maintenance of removable partial dentures in the middle category (54%). Most of elderly had incidence of gingivitis (64%). Based on the chi square test showed that p-value was 0,000. Conclusion: The behavior of maintenance of removable partial dentures corelate with the incidence of gingivitis in elderly.